Nexus between entrepreneurship and poverty reduction: regression analysis of causality (Journal of Economic Research & Business Administration, 2025)
Poverty reduction remains a key priority of Kazakhstan’s socio-economic policy. While entrepreneurship is widely acknowledged as a driver of economic growth, its association with poverty alleviation in the country remains insufficiently explored. A comprehensive analysis of this relationship is essential for enhancing policy effectiveness.This study examines the associations between entrepreneurial activity, business incentives, and poverty reduction in Kazakhstan. The Human Development Index (HDI) is employed as the dependent variable, as it encapsulates not only income levels but also access to education and healthcare.The study applies linear, logarithmic, and semi-logarithmic regression models, addressing potential issues of multicollinearity and autocorrelation. The independent variables include entrepreneurial activity, business development incentives, trade openness, urbanization, and corruption control.The results confirm that entrepreneurship and business incentives play a crucial role in poverty reduction. Increased entrepreneurial activity contributes to job creation, income growth, and improved access to essential services. Furthermore, the study highlights the significance of reducing administrative barriers and strengthening anti-corruption measures to foster business development. Additionally, urbanization and trade openness are identified as significant determinants of economic progress.Unlike traditional studies that focus solely on income-based measures, this research employs HDI as a comprehensive indicator of human development. The findings offer valuable insights for policymakers in designing effective entrepreneurship policies, optimizing regulatory frameworks, and enhancing governance mechanisms to promote sustainable economic growth and poverty reduction in Kazakhstan.Key words: poverty, entrepreneurship, Human development index, urbanization, trade.